2022
DOI: 10.3389/fnetp.2022.866101
|View full text |Cite
|
Sign up to set email alerts
|

Optical Ultrastructure of Large Mammalian Hearts Recovers Discordant Alternans by In Silico Data Assimilation

Abstract: Understanding and predicting the mechanisms promoting the onset and sustainability of cardiac arrhythmias represent a primary concern in the scientific and medical communities still today. Despite the long-lasting effort in clinical and physico-mathematical research, a critical aspect to be fully characterized and unveiled is represented by spatiotemporal alternans patterns of cardiac excitation. The identification of discordant alternans and higher-order alternating rhythms by advanced data analyses as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…The critical combination of both properties, however, is crucial to maintain cellular integrity and functionality, as we have shown in this study. More sensitive myocyte cultures, such as embryonic and inducible pluripotent stem cells [20], as well as primary cultures of neonatal animals [2], may be affected even stronger, and therefore, might be responsible for the life-threatening induction of alternans, where mechanoregulation, tissue arrangement and synchonization dynamics play an essential role [2,52,53]. The methodology and results presented in this manuscript provide a fundamental platform to investigate more complex myocyte dynamics, such as the proliferation dynamics of cells in crowded cell environments and differentiation dynamics of pluripotent cells in organoids, as cell shape may be stabilized by the tight junctions of neighboring cells and therefore also influence actin depolymerization dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The critical combination of both properties, however, is crucial to maintain cellular integrity and functionality, as we have shown in this study. More sensitive myocyte cultures, such as embryonic and inducible pluripotent stem cells [20], as well as primary cultures of neonatal animals [2], may be affected even stronger, and therefore, might be responsible for the life-threatening induction of alternans, where mechanoregulation, tissue arrangement and synchonization dynamics play an essential role [2,52,53]. The methodology and results presented in this manuscript provide a fundamental platform to investigate more complex myocyte dynamics, such as the proliferation dynamics of cells in crowded cell environments and differentiation dynamics of pluripotent cells in organoids, as cell shape may be stabilized by the tight junctions of neighboring cells and therefore also influence actin depolymerization dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Alternans patterns, whether APD-driven or Ca-driven, can exhibit spatial in-phase behavior (concordant alternans-CA), where the entire tissue alternates between long/high and short/low phases, or out-of-phase behavior (discordant alternans-DA), where neighboring subregions alternate between long and short phases or high and low phases with transitions occurring via non-alternating areas (nodal lines) (Hörning et al 2017). Complex behaviors and higher-order rhythms have been confirmed through various spectral analyses (Loppini et al 2022), and advances in imaging techniques (Laurita and Singal 2001, Marina-Breysse et al 2021, that allow simultaneous recordings of voltage and calcium dynamics, have enabled novel multi-field and multi-scale characterization of spatiotemporal alternans phenomena (figure 1).…”
Section: Introductionmentioning
confidence: 89%
“…However, the differences in tissue dynamics could also be due to scar distributions, which are highly variable from one heart to the next. Accordingly, an accurate study of the optical ultrastructure (Loppini et al 2022) could be further associated with the proposed integral analyses toward a more comprehensive investigation of the underlying mechanisms extracted from fluorescence optical signals. Preliminary results in this direction are provided in figure S8, supplementary materials.…”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…Experimentally, optogenetically modified cardiac cells offer new ways for implementing and testing alternative approaches for defibrillation ( Bruegmann et al, 2016 ; Hussaini et al, 2021 ). Progress has also been been made combining experimental data with numerical modelling, for example, for studying spatiotemporal alternans patterns of cardiac excitation ( Loppini et al, 2022 ). Recent numerical studies have shown that pulse timing is crucial for termination success ( Steyer et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%